2020
DOI: 10.3390/polym12040950
|View full text |Cite
|
Sign up to set email alerts
|

Silane Effect of Universal Adhesive on the Composite–Composite Repair Bond Strength after Different Surface Pretreatments

Abstract: This study investigated the impact of a separate silanization step on the repair bond strength of composite substrates using a universal adhesive after various mechanical surface treatments. Composite specimens were aged and exposed to the following mechanical roughening treatments: diamond bur abrasion, aluminum oxide sandblasting, or silica coating. The specimens were then either left untreated or conditioned with universal adhesive (Scotchbond Universal), or a silane coupling agent was applied before the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 53 publications
2
18
1
Order By: Relevance
“…In this context, the factors of size, speed, and type of the applied abrasive particles also correlate with material removal of the substrate composite and affect the surface morphology [ 11 , 20 ]. The chosen particle size of 50 µm [ 11 , 12 , 13 , 14 , 17 ] and application time of 10 s [ 13 , 29 ] are thus in accordance with other studies examining repair procedures.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this context, the factors of size, speed, and type of the applied abrasive particles also correlate with material removal of the substrate composite and affect the surface morphology [ 11 , 20 ]. The chosen particle size of 50 µm [ 11 , 12 , 13 , 14 , 17 ] and application time of 10 s [ 13 , 29 ] are thus in accordance with other studies examining repair procedures.…”
Section: Discussionsupporting
confidence: 66%
“…However, the results of the present study showed no significant difference when sandblasting was performed from these working distances compared to the inherent incremental bond strength. Indeed, many studies on composite repair performed sandblasting with air abrasion particles at a working distance of 5 mm [ 12 , 13 , 27 , 29 ], while others operated at a distance of 10 mm [ 14 , 18 ], 20 mm [ 21 ] or even 30 mm [ 22 ]. In this context, the factors of size, speed, and type of the applied abrasive particles also correlate with material removal of the substrate composite and affect the surface morphology [ 11 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the present study, no capping layer was placed on top of the flowable bulk-fill materials under investigation. The universal adhesive Scotchbond Universal was selected because it showed reliable results in both laboratory [ 33 , 34 , 35 ] and clinical studies [ 36 , 37 ]. To ensure time-saving application in the treatment of children, the universal adhesive was used in self-etch mode and thus was in line with previous studies [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of modern so-called "universal" or "multi-mode" adhesive systems has greatly increased due to their convenient handling. These simplified single bottle adhesives are applicable in the two aforementioned approaches, depending on the clinical situation and the clinician's preference [16][17][18][19][20][21][22][23]. The composition of universal adhesives includes acidic functional monomers that are able to etch dental hard tissues according to their functional group and establish micro-mechanical and chemical bonding with the tooth surface [5,15,20,24,25] and various restoration materials [6,22,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…These simplified single bottle adhesives are applicable in the two aforementioned approaches, depending on the clinical situation and the clinician's preference [16][17][18][19][20][21][22][23]. The composition of universal adhesives includes acidic functional monomers that are able to etch dental hard tissues according to their functional group and establish micro-mechanical and chemical bonding with the tooth surface [5,15,20,24,25] and various restoration materials [6,22,24,26]. Controversial results were found for dentin bond strength when an additional phosphoric acid etching step was carried out prior to the application of universal adhesives, ranging from similar to higher bond strengths compared to the self-etch application mode [20,21,[27][28][29][30][31], especially for ultra-mild adhesives [2,4,20].…”
Section: Introductionmentioning
confidence: 99%